A Comparative Study of Soil and Foliar Nickel Application on Growth, Yield and Nutritional Quality of Barley (Hordeum Vulgare L.) Grown in Inceptisol. Issue 11 (17th June 2021) - Kumar, Omkar; Singh, Satish Kumar; Patra, Abhik; Latare, Ashish; Yadav, Sobh Nath
ABSTRACT: Nickel (Ni) deficiency is common in intensively cultivated soils. As Ni is a costly input, thus, judicious use in agriculture is needed to address its deficiency economically. In view of deficiency of Ni, a field experiment was conducted to evaluate the responses for soil (SA), foliar (FA) and combination of these two methods of Ni application on growth, yield, nutritional quality and bio-chemical properties of soil using barley as a test crop. Foliar application of 0.2% NiSO4 significantly enhanced growth, yield, and nutrients concentration in grain as compared to SA. The highest grain and straw yield was in 5.0 kg SA Ni ha −1  + 0.2% FA of NiSO4 but it was statically at par with 0.2% FA of NiSO4 . Application of 10 kg SA Ni ha −1  + 0.2% FA of NiSO4 resulted in a significant yield decrease. The maximum bacterial population was with 5 kg SA Ni ha −1, whereas actinomycetes population in 7.5 kg SA Ni ha −1 . However, higher dose of Ni had a synergistic effect on the fungal population and urease enzyme activity. It was inferred that 0.2% FA of NiSO4 may be economically used over soil application to mitigate the deficiency of Ni in barley.